Preclinical safety study of a fully implantable, sub-scalp ring electrode array for long-term EEG recordings. (1st June 2022) - Benovitski, Yuri B; Lai, Alan; Saunders, Alexia; McGowan, Ceara C; Burns, Owen; Nayagam, David A X; Millard, Rodney; Harrison, Mark; Rathbone, Graeme D; Williams, Richard A; May, Clive N; Murphy, Michael; et al.
Abstract: Objective . Long-term electroencephalogram (EEG) recordings can aid diagnosis and management of various neurological conditions such as epilepsy. In this study we characterize the safety and stability of a clinical grade ring electrode arrays by analyzing EEG recordings, fluoroscopy, and computed tomography (CT) imaging with long-term implantation and histopathological tissue response. Approach . Seven animals were chronically implanted with EEG recording array consisting of four electrode contacts. Recordings were made bilaterally using a bipolar longitudinal montage. The array was connected to a fully implantable micro-processor controlled electronic device with two low-noise differential amplifiers and a transmitter-receiver coil. An external wearable was used to power, communicate with the implant via an inductive coil, and store the data. The sub-scalp electrode arrays were made using medical grade silicone and platinum. The electrode arrays were tunneled in the subgaleal cleavage plane between the periosteum and the overlying dermis. These were implanted for 3–7 months before euthanasia and histopathological assessment. EEG and impedance were recorded throughout the study. Main results . Impedance measurements remained low throughout the study for 11 of 12 channels over the recording period ranged from 3 to 5 months. There was also a steady amplitude of slow-wave EEG and chewing artifact (noise). The post-mortem CT and histopathology showed the electrodes remained in the subgaleal plane in 6 of 7 sheep. There was minimal inflammation with a thin fibrotic capsule that ranged from 4 to 101 μ m. There was a variable fibrosis in the subgaleal plane extending from 210 to 3617 μ m (S3–S7) due to surgical cleavage. One sheep had an inflammatory reaction due to electrode extrusion. The passive electrode array extraction force was around 1 N. Significance . Results show sub-scalp electrode placement was safe and stable for long term implantation. This is advantageous for diagnosis and management of neurological conditions where long-term, EEG monitoring is required.